Aryl Hydrocarbon Receptor Modulates Carcinogenesis and Maintenance of Skin Cancers - Hidaka, Takanori; Fujimura, Taku; Aiba, Setsuya (Frontiers in Medicine, 2019)
The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that responds to a wide range of chemicals, including chemical carcinogens such as dioxins and carcinogenic polyaromatic hydrocarbons, and induces a battery of genes associated with detoxification, proliferation, and immune regulation. Recent reports suggest that AHR plays an important role in carcinogenesis and maintenance of various types of skin cancers. Indeed, AHR is a susceptibility gene for squamous cell carcinoma and a prognostic factor for melanoma and Merkel cell carcinoma. In addition, the carcinogenic effects of ultraviolet (UV) and chemical carcinogens, both of which are major environmental carcinogenetic factors of skin, are at least partly mediated by AHR, which regulates UV-induced inflammation and apoptosis, the DNA repair system, and metabolic activation of chemical carcinogens. Furthermore, AHR modulates the efficacy of key therapeutic agents in melanoma. AHR activation induces the expression of resistance genes against the inhibitors of V600E mutated B-Raf proto-oncogene, serine/threonine kinase (BRAF) in melanoma and upregulation of programmed cell death protein 1 (PD-1) in tumor-infiltrating T cells surrounding melanoma. Taken together, these findings underscore the importance of AHR in the biology of skin cancers. Development of therapeutic agents that modulate AHR activity is a promising strategy to advance chemoprevention and chemotherapy for skin cancers.